Pengembangan Media Visual Gerak Untuk Meningkatkan Keterampilan Bercerita Siswa Tema 8 Subtema 3 Kelas IV SDN 091355 Urung Panei - Pakpahan, Ruth Imelda; Simanungkalit, Erlinda; Sitohang, Risma; Tamba, Robenhart; Faisal, Faisal (Universitas Labuhanbatu, 2023)
The aim of this research is to prove the effectiveness of visual motion learning media products in Class IV Indonesian language learning at SDN 091355 Urung Panei. The type of research used in this research is research and development (R&D) with a 4D model. This research and development was carried out at SDN 091355 Urung Panei which is located in Purba District, Simalungun Regency, North Sumatra. The subjects of this research and development were 26 class IV students at SD 091355 Urung Panei. The object of this research is the development of motion visual media in Indonesian language learning. The results of the research show that visual motion learning media is successful in improving student learning outcomes and increasing students' interest inlearning, and educational videos with animation are positive enough to be used in learning and meet the criteria